Designing, implementing and testing an intervention of affective intelligent agents in nursing virtual reality teaching simulations—a qualitative study - Loizou, Michael; Arnab, Sylvester; Lameras, Petros; Hartley, Thomas; Loizides, Fernando; Kumar, Praveen; Sumilo, Dana (Frontiers in Digital Health, 2024)
Emotions play an important role in human-computer interaction, but there is limited research on affective and emotional virtual agent design in the area of teaching simulations for healthcare provision. The purpose of this work is twofold: firstly, to describe the process for designing affective intelligent agents that are engaged in automated communications such as person to computer conversations, and secondly to test a bespoke prototype digital intervention which implements such agents. The presented study tests two distinct virtual learning environments, one of which was enhanced with affective virtual patients, with nine 3rd year nursing students specialising in mental health, during their professional practice stage. All (100%) of the participants reported that, when using the enhanced scenario, they experienced a more realistic representation of carer/patient interaction; better recognition of the patients' feelings; recognition and assessment of emotions; a better realisation of how feelings can affect patients' emotional state and how they could better empathise with the patients.